Planning health promotion programs : an intervention mapping approach (San Francisco, Calif. : Jossey-Bass, 2016)
Lanning Health Promotion Programs: An Intervention Mapping Approach, Fourth Edition presents a health promotion planning framework (called Intervention Mapping) as a series of steps, tasks, and processes to help health promotion and health education planners develop theory- and evidence-based programs. The book guides students and practitioners through the planning process and reviews the most common theoretical approaches. Because no one theoretical model completely predicts or mediates health behavior or environmental changes, the book presents a system to help intervention developers choose useful theories and integrate relevant constructs from multiple theories to describe health problems and develop health promotion and health education solutions. The first three editions of Planning Health Promotion Programs have influenced the methods and practices for health promotion planning in both academic and practice settings. With the fourth edition, the authors propose tightening and streamlining the overall text and presentation. The book will incorporate several recent trends in education for public health: competency-based training (enhancing the skills and competencies of students, practitioners, and researchers in the development of theory- and evidence-based health promotion interventions) and inter-professional education (skills to work across disciplines to improve the health of individuals and communities). This will make the text more readily-accessible and practical to both students and practitioners. Other changes include updates on all theories, new examples and case studies, and new sections emphasizing implication for practice in each step of the planning process.
Keywords: Evidence-Based Medicine; Gezondheidspromotie; Gezondheidsvoorlichting; Health Education; Health Promotion; Health education; Health promotion -- Planning -- Methodology; Health promotion -- Planning; Health promotion; Planning Techniques; Program Development -- Methods